Phrasem-Konstruktionen im deutsch-polnischen Vergleich anhand des Projekts „A Multilingual Repository of Phraseme Constructions in Central and Eastern European Languages (PhraConRep)“ (CA22115) - Dominika Janus; Marcelina Kałasznik; Krystian Suchorab; Joanna Szczęk (Linguistische Treffen in Wrocław)
When learning and using a foreign language, language users must not only adhere to the grammatical rules of a particular language, but also have knowledge of which words occur together. This is the knowledge of how to combine words and grammatical forms to create certain meanings in certain contexts. Against this background, phraseme constructions (in short: PhK) play an enormously important role in everyday communication, as they are usually ready-made components that are filled with corresponding lexical components in the respective contexts. The subject of this article are phraseme constructions that are being recorded lexicographically as part of the project “A Multilingual Repository of Phraseme Constructions in Central and Eastern European Languages (PhraConRep)” (CA22115), which started in November 2023. The source language of the project is German. As part of the project, around 300 phraseme constructions are to be recorded lexicographically in their entirety and provided with corresponding translation examples in the project languages. The article discusses the structure of the dictionary articles. The translation aspects in the German-Polish context are also discussed. In addition, difficulties in the area of German-Polish equivalence are highlighted. The PhK repository created as part of the project is the first such a broad-based project and can be considered a model in terms of the model-like characteristics of each recorded unit.